2015
DOI: 10.2514/1.j053771
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Corner Flow Separation on a Simplified Junction

Abstract: This study focuses on the corner flow separation occurring in a simplified wing-body junction composed of a NACA0015 twisted wing mounted on a flat plate at a Reynolds number based on the wing chord of Re c 1.2 × 10 6 . Wind-tunnel test measurements are carried out in the corner area including extensive oil-flow visualizations, high speed particle image velocimetry and unsteady pressure sensors. The analysis of the experimental database shows that the corner flow separation creates mean flow distortions that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
(35 reference statements)
2
10
0
Order By: Relevance
“…This behavior is consistent with Simpson (2001), who reports a stronger HSV with increasing AoA. Gand et al (2015) showed experimentally that the onset of corner separation is delayed by a stronger HSV, since fluid of higher momentum is pushed into the blade boundary layer. This beneficial inductive effect likewise depends on the distance to the blade.…”
Section: The Effect On Flow Separation and Its Driving Parameterssupporting
confidence: 89%
See 2 more Smart Citations
“…This behavior is consistent with Simpson (2001), who reports a stronger HSV with increasing AoA. Gand et al (2015) showed experimentally that the onset of corner separation is delayed by a stronger HSV, since fluid of higher momentum is pushed into the blade boundary layer. This beneficial inductive effect likewise depends on the distance to the blade.…”
Section: The Effect On Flow Separation and Its Driving Parameterssupporting
confidence: 89%
“…This phenomenon is typically found in the junction of the wing and the fuselage of transport aircraft (Levy et al, 2014;Vassberg et al, 2008) or in turbo-machinery cascades (Knezevici et al, 2010). Corner flows are highly influenced by a complex vortex system of primary and secondary vortices and have been investigated in great detail in experimental work addressing the effect of the horseshoe vortex (HSV) near the leading edge (see review paper of Simpson, 2001) and more recently by Gand et al (2015), also focusing on the trailing edge and analyzing the corner vortex. The latter authors found particular evidence that the Reynolds stresses are not aligned with the mean shear tensor, which means that anisotropy of turbulence is present in the region of corner flow separation.…”
Section: Corner Flow Separation Of Aerodynamically Shaped Junctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface streamlines pattern observed in Figs. 10c and 10f is also comparable to the flow separation that occurs at wing-body junctions at higher angles of attack [39], although the effective increase in angle of attack is, in this case, a consequence of slipstream contraction. In order to further investigate the flowfield at the square duct's corner, the flow's axial vorticity is shown in Fig.…”
Section: Time-averaged Effects (Ad Simulation)mentioning
confidence: 53%
“…Subsequently, the investigators re-designed the experiment with a twisted NACA 0015 wing on a plate. 25 This time, the corner flow separated in the experiment. Details were provided at a chord Reynolds number of 1.2 × 10 6 and angle of attack of 12 • , although other conditions were also investigated.…”
Section: Introductionmentioning
confidence: 97%